Interactive data visualization foundations, techniques, and applications - Ward, Matthew, 1955-; Grinstein, Georges G.; Keim, Daniel (CRC Press, Taylor & Francis Group, 2015)
This text provides all the theory, details, and tools necessary to build visualizations and systems involving the visualization of data. In color throughout, it explains basic terminology and concepts, algorithmic and software engineering issues, and commonly used techniques and high-level algorithms. Full source code is provided for completing implementations. This edition includes better quality figures and numerous new figures and new chapter on techniques for time-oriented data.